Iowa Birdline update, October 14, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for October 14, 1991. The highlights for the update include sightings of a Yellow-rumped Warbler, Blackpoll Warbler, Groove-billed Ani and an immature Northern Goshawk. Also included are handwritten notes with sightings of Sabine's Gulls, Varied Thrush and a female White-winged Scoter. Epson - sheet feed/flatbed